The Effect of Total Debt and Sales on Share Prices of Coal Companies Listed on the Indonesian Stock Exchange for the 2018-2021 Period - Michal Wasserbauer (Journal of Accounting and Finance Management, 2023)
This research aims to see the effect of total debt and sales on share prices in coal companies listed on the Indonesian Stock Exchange for the 2018-2021 period. The independent variables in this research include: total debt and sales, with the dependent variable being stock price. The data used in this research is secondary data, obtained from the Indonesian stock exchange. The sampling technique used accidental sampling to obtain a sample of 40 coal companies. The tests carried out were the t test, f test, and r-square coefficient of determination. Where secondary data has been tested for validity and reliability, and classical assumptions have been tested and all data is suitable for further analysis or data processing. The company financial data used covers 2018-2021 on the Indonesian Stock Exchange. Data processing uses the IBM SPSS version 27 data processing application. The results of this research show that: 1) Total debt has no partial and insignificant effect on the share prices of coal companies listed on the Indonesian Stock Exchange for the 2018-2021 period; 2) Sales have a partial positive and significant effect on the share prices of coal companies listed on the Indonesian Stock Exchange for the 2018-2021 period; and 3) Total debt and sales have a positive and significant effect on the share prices of coal companies listed on the Indonesian Stock Exchange for the 2018-2021 period simultaneously.